Design and Implementation of an Automatic Onion Slicer Based on ESP32 Microcontroller with Internet of Things Monitoring - Gaby Gabrielyn Tappangrara; Nur Samsam S; Muslimin; Sukriyah Buwardah (UPPM Poltek ATI Makassar, 2025)
The fried shallot business has significant market potential; however, production processes that still rely on manual labor can lead to inefficiency, inconsistency, and suboptimal production results. To address these issues, this study aims to design and develop an automatic onion slicing machine based on a microcontroller and the Internet of Things (IoT) to improve efficiency and monitor the fried shallot production process. The device is equipped with a microcontroller that controls the onion slicing mechanism in real time via a web- or mobile-based application. The results of this research are expected to help fried shallot entrepreneurs increase productivity, reduce human error, and accelerate the production process. Furthermore, this tool is expected to contribute to the development of a more modern and efficient fried shallot business.Keyword: Automatic Onion Slicer, ESP32, IoT, Production Automation, Remote Monitoring